THE DETERMINANTS OF PRIVATE SECTOR'S ROLE IN PROMOTING AGRICULTURAL KNOWLEDGE AND INFORMATION SYSTEM IN DAKHLIA GOVERNORATE, EGYPT - Hazem S. Kassem (Journal of Animal and Plant Sciences, 2016)
The growing complexity of the private sector in agricultural extension services provision has stimulated the debate on which determinants hamper its role in promotion of agricultural knowledge and information system. The aim of this paper was to analyze the coordination and cooperation relationships between the private sector and other actors in Dakhlia governorate along with the constraints faced by the private sector. Data were collected from fifty three board members of different agricultural companies who had attained the workshop at Mansoura University. The results showed no strong relationship between the private sector and the other actors. Moreover, financial and technical issues are the main constraints faced by the private sector. This study recommends a legal framework to realize cooperation and coordination in order to ensure synergy and integration among the actors.
Keywords: Private sector; Determinants; Agricultural extension; Knowledge; System; Egyp